Advances in Ubiquitous Networking Proceedings of the UNet'15 - Sabir, Essaïd; Medromi, Hicham; Sadik, Mohamed (Lecture Notes in Electrical Engineering, 2016)
This volume publishes new trends and findings in hot topics related to ubiquitous computing/networking. It is the outcome of UNet - ainternational scientific event that took place on September 08-10, 2015, in the fascinating city of Casablanca, Morocco. UNet'15 is technically sponsored by IEEE Morocco Section and IEEE COMSOC Morocco Chapter.